Characteristics of the monkeypox virus isolate obtained from the first patient in Russia and its sensitivity to 7-[N-(4-trifluoromethylbenzoyl)-hydrazinocarbonyl]-tricyclo-[3.2.2.0^2,4]non-8-en-6-carboxylic acid - Alena S. Ovchinnikova; Dmitrii A. Odnoshevsky; Alexey S. Kabanov; Sergey A. Bodnev; Oleg V. Pyankov; Oksana P. Os'kina; Maria V. Sivay; Andrey V. Bespalov; Tatyana V. Tregubchak; Larisa N. Shishkina; Oleg S. Taranov; Vladimir V. Zolin; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Since early May 2022, more than 90,000 cases of monkeypox virus infection have been reported in more than 70 countries around the World. This is the largest outbreak of monkeypox ever recorded outside of Africa.